Effect of the Microbiome on Intestinal Innate Immune Development in Early Life and the Potential Strategy of Early Intervention - Yang, Zhipeng; Liu, Xiangchen; Wu, Yanting; Peng, Jian; Wei, Hongkui (Frontiers in Immunology, 2022)
Early life is a vital period for mammals to be colonized with the microbiome, which profoundly influences the development of the intestinal immune function. For neonates to resist pathogen infection and avoid gastrointestinal illness, the intestinal innate immune system is critical. Thus, this review summarizes the development of the intestinal microbiome and the intestinal innate immune barrier, including the intestinal epithelium and immune cells from fetal to weaning. Moreover, the impact of the intestinal microbiome on innate immune development and the two main way of early-life intervention including probiotics and fecal microbiota transplantation (FMT) also are discussed in this review. We hope to highlight the crosstalk between early microbial colonization and intestinal innate immunity development and offer some information for early intervention.